IMPACT OF INTELLECTUALIZATION ON THE MANAGEMENT SYSTEM IN PUBLIC SERVICE ACTIVITIES IN SOCIETY 5.0 - Kryshtanovych, Myroslav (Socio-economic relations in the digital society, 2024)
The purpose of the study is to characterize the impact of intellectualization on the management system in public service activities in society 5.0. The main objective of this article is to determine the factors of intellectualization that significantly affect the effectiveness of management processes in public service. The essence of intellectualization and the management system in public service activities is studied, and an analysis of ordering hierarchies is conducted to identify key factors. The hierarchical analysis method is used. It is established that intellectualization contributes to the optimization of management decisions through the implementation of modern information technologies, improving the skills of employees and automating routine processes. The impact of intellectualization on increasing transparency, flexibility and adaptability of management structures in public service is characterized. The need to integrate innovative approaches to management is emphasized to ensure the effective operation of the public service in the conditions of rapid changes in society 5.0. It is proven that the implementation of intellectualized management systems contributes to improving the quality of public service provision, ensuring better interaction between state institutions and citizens.